Layer-by-layer electrostatic self-assembled coatings based on flaxseed gum and chitosan for Mongolian cheese preservation. (October 2021) - Lu, Zeyu; Saldaña, Marleny D.A.; Jin, Zhimin; Sun, Wuliang; Gao, Pengfei; Bilige, Menghe; Sun, Wenxiu
Abstract: Mongolian cheese, a daily essential dairy product of Mongolians, is nutritious but susceptible to microbial contamination. Edible coatings consisted of casein, chitosan and flaxseed gum were developed to extend the shelf life of Mongolian cheese by self-assembly on its surface. Due to the amphoteric properties of casein, positive and negative charges were obtained as a template by adjusting the isoelectric points. With chitosan as the positive charge provider and flaxseed gum as the negative charge provider, edible coatings were formed on the surface of Mongolian cheese by layer-by-layer electrostatic self-assembly technology. Chitosan inhibited the proliferation of internal microorganisms ( molds and yeasts ) when it was the innermost layer, and resisted the invasion of foreign microorganisms ( Escherichia coli and Staphylococcus aureus ) while it was the outermost layer. And, this effect became stronger with the increase of layer numbers. The layer-by-layer electrostatic self-assembly technology of polysaccharide not only improved the quality of Mongolian cheese but extended its shelf life. Highlights: A layer-by-layer electrostatic self-assembly technology was adopted. Self-assembled edible coating is composed of natural materials chitosan and flaxseed gum. The self-assembled coating has broad spectrum bacteriostatic action. Electrostatic self-assembled coating extended the shelf life of Mongolian cheese.